Perceptions of work environment, locus of control and financial well-being among Putrajaya employees - Mokhtar, Nuradibah; Abdul Rahim@Abdul Wahab, Husniyah (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2017)
In recent decades, the severe change in the world economy indicated by changes of GDP has triggered insightful effects on an individual’s well-being (Organization for Economic Co-operation and Development (OECD), 2013). Financial well-being play a big role in well-being of on individual (Kalia, 2016). As a matter of fact, Joo (2008) stated that financial well-being is a sub-element of general well-being which makes it among the five crucial elements of well-being (Rath & Harter, 2010b). Consequently, financial wellbeing research is increasingly popular in the 21st century (Rath & Harter, 2010a). Financial educators, coaches and practitioners work together hand-inhand to help people improve their financial lives and alleviate to a better financial well-being state.